Minat Belajar dalam Pembelajaran Daring Pada Masa Pandemi Covid-19 Siswa Kelas IV SD Negeri Kepohagung Rembang - Lutfiana, Estika Citra; Ysh, A. Y. Soegeng; Purnamasari, Veryliana (STKIP Andi Matappa Pangkep, 2022)
The purpose of this study was to determine interest in learning in online learning for fourth grade students of SD Negeri Kepohagung Rembang. In this study using a qualitative method with a descriptive approach. The data collection procedure used observation, interviews, questionnaires, and documentation. The results showed that interest in learning can be viewed from four indicators, namely feelings of pleasure, interest, attention, and involvement. Students' interest in learning is basically good, but due to the Covid-19 pandemic, student interest in learning has decreased, although not in all indicators. Students feel happier with face-to-face learning because online learning is less effective. Online learning is carried out using WhatsApp group media. However, students' desire to learn is still quite good, students still have curiosity about the material given by the teacher. In addition, students continue to work on and collect assignments according to the specified time limit, although sometimes students are still found who are late in submitting assignments. Some students still respond through WhatsApp groups, the three teachers provide material or just information even though they are passive so that teacher and student interaction is lacking.